RT-RPA-PfAgo detection platform for one-tube simultaneous typing diagnosis of human respiratory syncytial virus - Liao, Jia-Yu; Feng, Xue-Yong; Zhang, Jie-Xiu; Yang, Tian-Dan; Zhan, Min-Xuan; Zeng, Yong-Mei; Huang, Wei-Yi; Lian, Hao-Bin; Ke, Lin; Cai, Si-Si; Zhang, Nan-Fei; Fang, Jin-Wen; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Human respiratory syncytial virus (HRSV) is the most prevalent pathogen contributing to acute respiratory tract infections (ARTI) in infants and young children and can lead to significant financial and medical costs. Here, we developed a simultaneous, dual-gene and ultrasensitive detection system for typing HRSV within 60 minutes that needs only minimum laboratory support. Briefly, multiplex integrating reverse transcription-recombinase polymerase amplification (RT-RPA) was performed with viral RNA extracted from nasopharyngeal swabs as a template for the amplification of the specific regions of subtypes A (HRSVA) and B (HRSVB) of HRSV. Next, the Pyrococcus furiosus Argonaute (PfAgo) protein utilizes small 5’-phosphorylated DNA guides to cleave target sequences and produce fluorophore signals (FAM and ROX). Compared with the traditional gold standard (RT-qPCR) and direct immunofluorescence assay (DFA), this method has the additional advantages of easy operation, efficiency and sensitivity, with a limit of detection (LOD) of 1 copy/μL. In terms of clinical sample validation, the diagnostic accuracy of the method for determining the HRSVA and HRSVB infection was greater than 95%. This technique provides a reliable point-of-care (POC) testing for the diagnosis of HRSV-induced ARTI in children and for outbreak management, especially in resource-limited settings.